miRNAs may play a major role in the control of gene expression in key pathobiological processes in Chagas disease cardiomyopathy. - Laurie Laugier; Ludmila Rodrigues Pinto Ferreira; Frederico Moraes Ferreira; Sandrine Cabantous; Amanda Farage Frade; Joao Paulo Nunes; Rafael Almeida Ribeiro; Pauline Brochet; Priscila Camillo Teixeira; Ronaldo Honorato Barros Santos; Edimar A Bocchi; Fernando Bacal; et al. (Public Library of Science (PLoS), 2020)
Chronic Chagas disease cardiomyopathy (CCC), an especially aggressive inflammatory dilated cardiomyopathy caused by lifelong infection with the protozoan Trypanosoma cruzi, is a major cause of cardiomyopathy in Latin America. Although chronic myocarditis may play a major pathogenetic role, little is known about the molecular mechanisms responsible for its severity. The aim of this study is to study the genes and microRNAs expression in tissues and their connections in regards to the pathobiological processes. To do so, we integrated for the first time global microRNA and mRNA expression profiling from myocardial tissue of CCC patients employing pathways and network analyses. We observed an enrichment in biological processes and pathways associated with the immune response and metabolism. IFNγ, TNF and NFkB were the top upstream regulators. The intersections between differentially expressed microRNAs and differentially expressed target mRNAs showed an enrichment in biological processes such as Inflammation, inflammation, Th1/IFN-γ-inducible genes, fibrosis, hypertrophy, and mitochondrial/oxidative stress/antioxidant response. MicroRNAs also played a role in the regulation of gene expression involved in the key cardiomyopathy-related processes fibrosis, hypertrophy, myocarditis and arrhythmia. Significantly, a discrete number of differentially expressed microRNAs targeted a high number of differentially expressed mRNAs (>20) in multiple processes. Our results suggest that miRNAs orchestrate expression of multiple genes in the major pathophysiological processes in CCC heart tissue. This may have a bearing on pathogenesis, biomarkers and therapy.